Movable solar powered cold storage for fruits and vegetables - SHARMA, P K (The Indian Journal of Agricultural Sciences, 2021)
A solar powered portable cold storage system was designed and developed in 2017-18 for storage of fresh fruits and vegetables to increase the shelf life. The capacity of the cooling chamber is 3.88 m3. The cold store was operated atthree temperatures 8, 12 and 16ºC, respectively for 24 h. At 8ºC, the ranges of temperature and RH inside and outsidecold storage were 9.3–11ºC and 73.11–76.4% and 26.5–40.7ºC and 25.3–61%. At 12ºC, the ranges of temperature and RH inside and outside cold storage were 13–14.7 ºC and 68.2–77.7% and 28.7–42.1ºC and 26.0–45.5%. At 16ºC, the ranges of temperature and RH inside and outside cold storage were 17–18.1ºC and 72.9–79.3V and 29.5–43.9ºC  and 22.2–50.1%. An average difference in temperature and RH of three setting temperatures (8, 12 and 16ºC) were 23.47, 21.94 and 18.90ºC and 33.63, 39.77 and 39.44% respectively. The average cooling efficiency of the developed cold storage for three setting temperatures was 91.26, 89.69 and 87.06 % respectively. This environment helped in keeping the vegetables fresh for significantly longer time. This cold storage structure is very useful for rural areas where there is shortage of electricity or its supply is erratic for storage of fresh fruits and vegetables.